Electroconvulsive Therapy in Transgender and Gender Diverse Population: A Case Report and Review of Literature - Lachlan Draper; Ashis Vikas; Subhash Das; Suresh Yadav; Frances Walker; Ivona Bandilovska (Case Reports in Psychiatry)
Objective. Present a case of a transgender and gender diverse (TGD) individual receiving gender affirming hormone therapy (GAHT) who presented with first episode bipolar mania and received electroconvulsive therapy (ECT). To understand the safety and efficacy of ECT in the TGD population including those receiving GAHT through literature review. Materials and Methods. Case report using informed consent from an individual TGD patient who received ECT. A review of the literature was conducted using PubMed, Embase, and Medline. Results. The case illustrated safe and effective ECT use in a TGD individual receiving GAHT. Eight studies were reviewed. GAHT has been reported to interfere with certain anaesthetic agents used in ECT. ECT appeared to be a safe and effective treatment in the TGD samples in those studies. Conclusion. There is limited literature on the safety and efficacy of ECT for TGD individuals receiving GAHT. More research is required to address mental health inequalities in this population and to support safe and effective gender affirming treatment modalities.